Intracellular Delivery of Short Interfering RNA in Rat Organ of Corti Using a Cell-penetrating Peptide PepFect6 - Suvarna Dash-Wagh; Stefan Jacob; Staffan Lindberg; Anders Fridberger; Ülo Langel; Mats Ulfendahl (Elsevier, 2012)
RNA interference (RNAi) using short interfering RNA (siRNA) is an attractive therapeutic approach for treatment of dominant-negative mutations. Some rare missense dominant-negative mutations lead to congenital-hearing impairments. A variety of viral vectors have been tested with variable efficacy for modulating gene expression in inner ear. However, there is concern regarding their safety for clinical use. Here, we report a novel cell-penetrating peptide (CPP)-based nonviral approach for delivering siRNA into inner ear tissue using organotypic cultures as model system. PepFect6 (PF6), a variant of stearyl-TP10, was specially designed for improved delivery of siRNA by facilitating endosomal release. We show that PF6 was internalized by all cells without inducing cytotoxicity in cochlear cultures. PF6/siRNA nanoparticles lead to knockdown of target genes, a housekeeping gene and supporting cell-specific connexin 26. Interestingly, application of PF6/connexin 26 siRNA exhibited knockdown of both connexin 26 and 30 mRNA and their absence led to impaired intercellular communication as demonstrated by reduced transfer of calcein among the PF6/connexin 26-siRNA-treated cells. Thus, we conclude that PF6 is an efficient nonviral vector for delivery of siRNA, which can be applied as a tool for the development of siRNA-based therapeutic applications for hearing impairments.